Asthma and allergic diseases : physiology, immunopharmacology, and treatment : fifth international symposium - Marone, G. (Gianni) (Academic Press, 1998)
This book updates the previous coverage of the mechanisms and mediators of asthma and its treatment. It presents articles by the foremost names in the field. Key Features * Updates the previous coverage of the mechanisms and mediators of asthma and its treatment * Presents articles by the foremost names in the field * Includes over 92 figures and 12 tables.